Theoretical Review for the Influencing Factors of Healthy Lifestyle on the Mental Health and well-being of Music College Students - WANG, TING; HAMID, JUNAINAH ABD; THAM, JACQULINE (International Journal of Multidisciplinary Research and Studies, 2023)
Physical and mental health are prerequisites for college students to finish their studies and achieve their personal ideals and values, as well as a fundamental condition for the judicious use of educational resources. Many governments and individuals throughout the world have begun to recognize the critical importance of human behavior and lifestyle in supporting personal and social health. The "overall health concept" of physical, psychological, and social health, as well as WHO's positive health concept, have also attracted an increasing number of countries and people. Previous research indicates that the health of Chinese college students is not promising. In terms of physical quality, obesity and overweight, as well as vital capacity, have dramatically deteriorated; in terms of mental health, numerous mental diseases have emerged as major issues affecting the health of college students. Based on the overall state of mental health and demand characteristics of college students in music and art, and combined with the analysis of deep-seated reasons, for different gender, different family background, different grade, different professional music art stress According to the study, male students majoring in music had more conversation and heterosexual communication problems than female students, while students in rural areas had more problems than students in metropolitan areas. Subjective satisfaction is higher among music majors. When girls are not the sole child and come from students in rural areas, they have higher life satisfaction than boys.